(untitled) (Revista científica Olimpia, 2025)
Stomatological emergencies require immediate attention to relieve pain, prevent complications and intervene on infectious or hemorrhagic processes. In this context, Natural and Traditional Medicine (NTM) has been positioned as a safe, accessible and culturally accepted complementary alternative, especially in environments where access to pharmacological resources may be limited. This article aims to analyze the use and effectiveness of various modalities of MNT in the treatment of urgent stomatological conditions, such as acute dental pain, stomatitis, abscesses and minor hemorrhages, as well as their limitations. Based on a documentary and descriptive review, therapeutic strategies based on phytotherapy, apitherapy and acupuncture were identified with positive clinical results, although the need for greater standardization and rigorous scientific evidence is recognized.